The Impact of Google Suites Amidst the New Normal - Mobo, Froilan (Future Science / FSH-PH Publications, 2021)
The Novel Corona Virus has greatly made an impact in the global community and including business sectorial group. Sectoral business establishments were temporarily closed because of the strict quarantine protocol set by the Inter-Agency Task Force on COVID 19. Classes and Work were also suspended that is why we are experiencing delays in all transactions. The virus has shifted our global workforce into a cloud-based or virtual-based transaction because there are regulations that we need to follow regardless if that is private and public offices. Most of them used technological platform like Google Suites which includes office application and virtual transactions that will help our economy boost up.